The Role of Marketing in Supporting Entrepreneurship Development: A Study of Small and Medium Sized Enterprise (SMEs) - Nor Aziza, Abdul Aziz (2011)
Marketing is an important element in a successful of entrepreneurship development. Elements of the marketing mix can influence decision making in purchasing by consumers. Thus, this study was conducted to identify the role marketing in contributing towards the development of entrepreneurs in Small and Medium Sized Enterprises (SMEs). Type of sampling used in this study is simple random sampling in which about 90 people from Perlis involving government agencies, entrepreneurs and consumer products. The data created is descriptive and regression analysis. The four elements of the marketing mix have a positive relationship with their development. The finding of this study showed that there is significant correlation between the product and distribution channels with their development. Therefore price and promotion factors have no significant relationship with entrepreneurship development. In the future research should be focus more on those elements.